A new species and palinotaxonomy of Besleria (Gesneriaceae) from the cloud forest of Valle del Cauca, Colombia - Cortés-Ceballos, Olga Lorena; Giraldo-Rodríguez, Andrés; Torresgonzález, Alba Marina; Enrique Moreno, J.; Gasparino, Eduardo Custódio [UNESP] (Magnolia Press, 2021)
We describe and illustrate a new species of Besleria (Gesneriaceae) from the department of Valle del Cauca, Colombia. This new species is morphologically similar to B. florida, B. microphylla, B. silverstoneana, and B. solanoides. We include a morphological key to distinguish B. brevisepala from similar species. We also studied pollen morphology to provide support for taxonomic differences among Besleria species from the Andean forest of Colombia. We investigated the pollen characteristics of the genus and assessed their use for taxonomic differentiation in this group through light and electron microscopy. Pollen grains were subjected to acetolysis, measured, photographed, and described qualitatively. We analyzed qualitative and quantitative data using descriptive and multivariate statistics. The pollen grains of Besleria were monad, isopolar, small, with circular amb; oblate to suboblate, 3-porate, with circular to oval pores, without annulus, operculate, and with vestibulum. The exine was tectate, perforate, and microreticulate with narrow muri and small lumina of slightly different shape and dimension. Our results confirm that Besleria is a eurypalynous genus, which allowed the identification of pollen morphological characteristics that are important for species differentiation.